The Being of Analogy - Roderick, Noah (New Metaphysics, 2016)
Similarity has long been excluded from reality in both the analytical and continental traditions. Because it exists in the aesthetic realm, and because aesthetics is thought to be divorced from objective reality, similarity has been confined to the prison of the subject. In The Being of Analogy, Noah Roderick unleashes similarity onto the world of objects. Inspired by object-oriented theories of causality, Roderick argues that similarity is ever present at the birth of new objects. This includes the emergent similarity of new mental objects, such as categories-a phenomenon we recognize as analogy. Analogy, Roderick contends, is at the very heart of cognition and communication, and it is through analogy that we can begin dismantling the impossible wall between knowing and being.